Makna Komunikasi Antarpersona dalam Membina Hubungan Persahabatan - Naufal Fahrurrobby; Alex Sobur (UNISBA Press, 2023)
Abstract. This research is entitled Interpersonal Communication Meaning in Building Friendship (Roland Barthes' Semiotics Analysis in The Bad Guys Film). The purpose of this research is to find out denotative meaning, connotative meaning and interpersonal communication myth in building friendship in The Bad Guys film. The Bad Guys film describe the friendship story of a famous animal bandits, The Bad Guys, the members are Mr. Wolf, Mr. Snake, Mr. Shark, Mr. Piranha and Mrs. Tarantula. This film tells there is a conflict that arise because of the misunderstanding among the gang and it causes the strained of their friendship, thus the characters in this film applied interpersonal communication in solving the conflict. Constructivist paradigm is applied to this research with qualitative descriptive method and Roland Barthes' semiotics approach. The data collecting technique employed in this research is observing and literary study. The researcher did the direct research to the research object intended to collect the required information. The result of this research shows there are denotative meaning, connotative meaning, and the meaning of interpersonal communication myth in building friendship in